PROPHYLACTIC ANTIEMETIC THERAPY WITH ONDANSETRON, DEXAMETHASONE AND COMBINED ONDANSETRON AND DEXAMETHASONE IN PATIENTS UNDERGOING LAPAROSCOPIC CHOLECYSTECTOMY UNDER GENERAL ANAESTHESIA (GA) - Nadia Bano; Nazim Hayat; A.G Rehan (Journal of University Medical & Dental College, 2017)
ABSTRACT: OBJECTIVE: The aim of this study was to find a better prophylaxis against postoperative nausea and vomiting (PONV) in patients undergoing laparoscopic cholecystectomy. STUDY DESIGN: A randomized control study was carried out for comparison. SETTING & DURATION: This study was conducted at department of anaesthesia and intensive care, Madinah Teaching Hospital, Faisalabad from January 2015 to July 2015. SAMPLE SIZE: The study population consisted of 90 ASA I & II status patients undergoing laparoscopic cholecystectomy under general anaesthesia. METHODS: The patients were randomly divided into three groups A, B and C. Group A patients were to receive prophylactic Dexamethasone, group B patients were to receive both Ondansetron and Dexamethasone and group C patients were to receive Ondansetron preoperatively. Postoperative nausea and vomiting was recorded and compared between three groups in PACU (Post anaesthesia care unit) for one hour and surgical ward for 23 hours respectively. RESULTS: It was observed that group B (combined Dexamethasone and Ondansetron group) patients had significantly less postoperative nausea and vomiting as well as less requirement for rescue antiemetics postoperatively as compared to group A (Dexamethasone group) and C (Ondansetron group) patients. The frequency of nausea and vomiting was 0% and 3.3% in group B as compared to 30% and 30% in group A and 16.7% and 23.3% in group C respectively. Rescue antiemetics were used in 6.7% patients in group B as compared to 40% patients in group A and 23.3% patients in group C. CONCLUSION: It is concluded that combined Dexamethasone and Ondansetron offer effective prophylaxis against postoperative nausea and vomiting in patients undergoing laparoscopic cholecystectomy as compared to Dexamethasone and Ondansetron alone.